ELECTRONIC EDUCATION IN SCHOOL MANAGEMENT - PISONOVA, Maria (Trends in education, 2008)
Accession refers about ability of application of electronic education in development coming and recent controlling employees of school a school institutions.
Keywords: electronic education; modules; mission of the project; abstract of modules.